The impact of Pandemic COVID-19 on cases of Borreliosis infection in 2020 - Karolina Rogulska; Patrycja Piątek; Konrad Grzeszczak (Kazimierz Wielki University, 2021)
Borreliosis (Lyme borreliosis; Lyme disease) is a zoonotic disease caused by spirochetes from the genus Borrelia. In humans, the accidental host of ticks, the infection is transmitted by the bite of the tick - the spirochetes are present in the salivary glands of the tick. Any of the three forms of tick: larva, nymph and adult can be responsible for infection. The most common threats to humans are Borrelia burgdorferii sensu stricto, Borrelia garinii and Borrelia afzelii occurring mainly in Europe. Lyme disease is a complex, multi-stage disease and progresses in 3 stages. The targeted treatment of Lyme disease is based on the administration of antibiotics. The introduction of antibiotics in the early stages of Lyme borreliosis offers a good chance of a complete cure. Lyme disease is a major epidemiological problem in the world. In Europe, the average number of cases per year remains at 65,400. In Poland, the number of infections annually reaches several tens of thousands. According to the National Institute of Hygiene of Poland, which keeps statistics of epidemiological reports, a total of 83,495 people fell sick with Lyme disease in Poland between 2016 and 2019. Whereas in 2020, the number of cases of Lyme disease decreased to 12933. The reason for this is undoubtedly the COVID-19 pandemic, which has dominated health care and focused all the attention of medical workers. This review shows that Lyme borreliosis is a dangerous disease with a high risk of complications. A quick diagnosis is crucial in the therapeutic process. An algorithm should be developed in order to distinguish other diseases from Lyme disease and thus enable an early reaction and treatment.